Mempelajari Proses Letusan Gunung Berapi melalui Eksperimen - Putri Chintya; Alfina Andriani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Volcanic eruptions release hazardous materials that can harm living things around them, so it is important to be aware of this. The adverse effects include dirty air from volcanic ash containing toxic gases such as sulfur dioxide, hydrogen sulfide, and nitrogen dioxide, as well as hazardous dust. This study aims to help students better understand how to prepare for a disaster, so that they can reduce the potential for harm. The research used in this study is qualitative. The subjects in this study were fifth grade students of SD Negeri 050750 Pangkalan Brandan, Langkat Regency. The results of this study indicate that if baking soda is added first, the volcano will erupt slowly and produce foam over time. But if vinegar is added first, the volcano will erupt much faster.